2017
DOI: 10.3390/catal7050132
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal-Modified Zirconium Phosphate Electrocatalysts for the Oxygen Evolution Reaction

Abstract: Zirconium phosphate (ZrP), an inorganic layered nanomaterial, is currently being investigated as a catalyst support for transition metal-based electrocatalysts for the oxygen evolution reaction (OER). Two metal-modified ZrP catalyst systems were synthesized: metal-intercalated ZrP and metal-adsorbed ZrP, each involving Fe(II), Fe(III), Co(II), and Ni(II) cations. Fourier transform infrared spectroscopy, X-ray powder diffraction, thermogravimetric analysis, and X-ray photoelectron spectroscopy were used to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 60 publications
0
40
0
Order By: Relevance
“…Our previous finding suggests that ZrP can serve as a support for transition metal-based OER catalysts and that the reaction occurs preferentially on the surface of the layered ZrP nanoparticles rather than the interlayer space [69]. Based on these results, we expected that exposing surface sites through exfoliation of ZrP could improve these catalytic systems.…”
Section: Metal-modified Exfoliated Zrpmentioning
confidence: 89%
See 2 more Smart Citations
“…Our previous finding suggests that ZrP can serve as a support for transition metal-based OER catalysts and that the reaction occurs preferentially on the surface of the layered ZrP nanoparticles rather than the interlayer space [69]. Based on these results, we expected that exposing surface sites through exfoliation of ZrP could improve these catalytic systems.…”
Section: Metal-modified Exfoliated Zrpmentioning
confidence: 89%
“…Its ability to confine catalysts, high thermal stability, stability under a wide range of pH values, and its overall robustness are all desired for an ideal support. In our work, we intercalated the earth-abundant transition metal cations Fe 2+ , Fe 3+ , Co 2+ , and Ni 2+ into ZrP and assessed these composite materials as OER electrocatalysts [69].…”
Section: Metal-modified Zrp Based Electrocatalysts For the Oermentioning
confidence: 99%
See 1 more Smart Citation
“…However, titanium phosphate can absorb sunlight, thus, most of Zr−Ti phosphates are used as photocatalysis material . Zirconium phosphate (ZrP) is generally used in conjunction with transition metal as electrocatalyst for water splitting, for example metal‐intercalated ZrP and metal‐adsorbed ZrP consisting of Ni 2+ , Fe 2+ , Fe 3+ and Co 2+ was active in OER for water oxidation in 0.1 M KOH and the activity of metal‐adsorbed ZrP is better than metal‐intercalated ZrP . Moreover, Zhao and co‐workers found that phosphate functionalized activated carbon (PAC) showed excellent electrocatalytic activity for the OER in an alkaline medium .…”
Section: Phosphate‐based Electrocatalysts For Water Splittingmentioning
confidence: 99%
“…By far, among the many hydrogen production methods (methane oxidation or reforming, etc. ), electrochemical water splitting is considered to be the most promising one at present, because it provides an apinoid strategy for renewable energy conversion and storage [7][8][9][10]. However, the semi-reaction in the process of water splitting, oxygen eVolution reaction (OER), is related to the continuous process of four proton-coupled electron transfer, which requires a higher overpotential at the anode and it therefore undergoes a sluggish reaction dynamics process [11][12][13].…”
Section: Introductionmentioning
confidence: 99%